ANALISIS PENERAPAN SISTEM INFORMASI AKUNTANSI PENJUALAN PESAWAT TELEPON PADA PT. DAMAI SEJATI MAKASSAR - Sultan Iskandar (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2014)
This study aims to identify and analyze the application of accounting information systems, in particular the implementation of systems and procedures implemented by the sale of PT. True peace Makassar. The analytical method used is descriptive comparative ie an analysis that describes and compares the application of accounting information systems sales , particularly in the application of systems and procedures implemented by the company sales with sales accounting information systems, in particular the implementation of systems and procedures for effective sales based on review of literature through the literature on systems and procedures sale